FEMALE IN THE HEALTHCARE: EXPLORING FEMALE NURSES MOTIVATION IN JAVANESE HOSPITALS, INDONESIA - Devita Rahmani (Universitas Brawijaya, 2023)
Javanese regions in Indonesia have been known to suffer from nurse shortages and low nurse motivation. These situations may hinder their performance. Gender and cultural aspects are essential to developing motivational strategies, but they are rarely considered in Indonesia. This study intended to explore the current situation in Javanese hospitals that affect the work motivation of female nurses. This study was a literature review. The keywords used for the search were “motivation,” “need* OR motive* OR goal* OR incentive* OR value*,” “work OR job OR career,” “policy OR regulation*,” “female OR women OR woman,” “nurse*,” “hospital*,” “government”, “Javanese OR Indonesia”, “low middle income country* OR developing country*” and “performance .”Data were obtained from electronic databases and grey literature. We used a conceptual framework to analyze 65 relevant articles. We found that female nurses in Javanese hospitals were seeking monetary means, supports to balance work-family, and means to boost their self-esteem and self-actualization. Government and hospital managers had been providing motivational incentives, yet the use of the incentives was still limited and inadequate. Hospital managers may provide a combination of financial and non-financial incentives to improve female nurses’ motivation, emphasizing non-financial incentives rather than financial incentives. More research is helpful in exploring what motivates Javanese female nurses.